Pengaruh Kurs dan BI Rate terhadap Dividend Payout Ratio pada Saham Idxenergy - Calvin Erlangga Putra; Annisa Alifa Ramadhani (Institut Nurul Islam Mojokerto, 2026)
Significant fluctuations in the dividend value of energy sector companies and the influence of external factors such as exchange rates and BI rates affect the company's financial performance and dividend distribution policy. This study aims to analyze the effect of exchange rate and BI Rate on dividend payout ratio in companies listed on IDXENERGY. The research method applied is quantitative through a panel data regression approach and processed using Eviews 13. The observation period is from 2020 to 2024 with 14 samples of energy sector companies. The research findings show that the exchange rate and BI Rate individually have no significant effect on the dividend payout ratio. Meanwhile, simultaneously the exchange rate and BI Rate have a significant effect on the dividend payout ratio. Keywords: Kurs, BI Rate, IDXENERGY, Dividend Payout Ratio.